ANALISIS PEMBELAJARAN LANGSUNG PADA KETERAMPILAN MENULIS PUISI BAHASA INDONESIA PADA KELAS XII IPS DI MA AT-TAUFIQ - Resdianto Permata Raharjo (STKIP PGRI Jombang, 2022)
Language skills consist of several skills including reading skills, speaking skills, listening skills and writing skills. Language is a tool to convey the information in mind that is conveyed directly by oral or by hand writing. Language has an important role in society because it is included in moral and civilized. A person said to be civilized by the utterance delivered includes the tone and meaning of the utterance delivered by the person. The main difference between humans and animals lies in two things, the first ability to think and the second ability to speak, humans can think because there is language and without human language can not think abstractly, without human language can not communicate and thoughts to others. Therefore humans must be able to master the language with good language. The recognized learning strategy can facilitate teaching to achieve goals in the learning process. The success of learning objectives is often generated by the ability of the teacher or instructor in carrying out strategies, mastering the material to be delivered and forming good communication in the classroom.